New Mixaderus species from the Mascarene Islands (Coleoptera: Aderidae) - Gompel, Nicolas (Zootaxa, 2021)
Following a previous revision of species of the genus Mixaderus Collado & Alonso-Zarazaga, 1996 (Coleoptera: Aderidae) from Madagascar and the Mascarene islands, I describe here six new species from the same genus from La Réunion and Mauritius: Mixaderus reunionensis n. sp.; Mixaderus chassaini n. sp.; Mixaderus lemagneni n. sp.; Mixaderus tamisieri n. sp.; Mixaderus voisini n. sp.; Mixaderus mauritiensis n. sp. I also provide an updated key to the Mixaderus species from the Mascarene archipelago.